Acordo sobre Medidas de Investimento Relacionadas ao Comércio (TRIMs): Entraves às políticas industriais dos países em desenvolvimento - Samo Sérgio Gonçalves (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The evolution of the international trade law has reduced the scope for States to adopt public policies oriented to economic development. The loss of sovereignty in this field has been wider for developing countries, since the norms that regulate the international economy have expressed, mainly, the interests of the developed world. This article aims to study one of the issues in which the capacity of nations to intervene has been drastically reduced: the Trade-Related Investment Measures (TRIMs) treaty, signed under the aegis of World Trade Organization (WTO). The objective is to demonstrate that TRIMs has precluded developing nations from implementing industrial policies.
Keywords: K330; 330